Enhancing Students’ Creative Thinking in Fine Arts Through Modern Educational Technologies - Muzafarova Sanobar Murodullayevna (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Abstract: This article explores the role of modern educational technologies in enhancing students’ creative thinking in fine arts education. It examines the impact of interactive tools, digital platforms, and project-based learning on students’ compositional thinking, aesthetic decision-making, and problem-solving abilities. The study emphasizes the integration of technology with pedagogical strategies to create a dynamic learning environment that supports both individual creativity and collaborative artistic work. Additionally, the article discusses the teacher’s role in facilitating digital and interactive approaches to maximize students’ creative potential.